Maternal nutrition and neurogenesis - Fabianová , Kamila; Babeľová, Janka; Popovičová, Alexandra; Fabian, Dušan; Martončíková, Marcela; Raček, Adam; Račeková, Enikő (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):309